BCR-ABL1 is a secondary event after JAK2V617F in a patient with essential thrombocythemia who develop chronic myeloid leukemia. Issue 4 (1st August 2022) - Zhang, Yanqing; Bi, Hailiang; Wang, Ying; Chen, Long; Pan, Jiaqi; Xu, Ping; Wang, Wei; Yang, Shaobin
Abstract : Several cases such as myeloproliferative neoplasms (MPN) with the coexistence of JAK2 and BCR-ABL have been reported. However, cases of transformation of essential thrombocythemia (ET) into chronic myeloid leukemia (CML) during the disease progression were rarely reported. Here, we report the case of a patient with JAK2 V617F - positive ET who subsequently acquired BCR–ABL1, which transformed the disease into CML after 10 years from the initial diagnosis. In this study, we dynamically monitored JAK2 V617F and BCR-ABL and observed multiple gene mutations, including IDH2, IDH1, ASXL1, KRAS, and RUNX1. It is important to be aware of this potentially clone evolution in disease progression.